Urban Labor Markets in Sub-Saharan Africa - De Vreyer, Philippe; Roubaud, François (Washington, DC: World Bank and Agence Française de Développement, 2013)
The population of Sub-Saharan Africa stood at 854 million in 2010. Annual population growth averaged 2.5 percent, with a relatively high sustained fertility rate, fostered by the fact that two-thirds of the population is under 25. The region has the highest proportion of poor people in the world, with 47.5 percent of its population living on less than $1.25 a day, as measured in terms of purchasing power parity in 2008. It is also the only region in which the number of poor is still rising. This book contributes to knowledge on the functioning of urban labor markets in Sub-Saharan Africa by investigating following questions: which individuals lack access to employment or are employed beneath their capacities; does education improve working conditions?; what opportunities does the labor market offer to climb the social ladder?; is the lack of good-quality jobs for adults and the poverty it implies one of the reasons for the prevalence of child labor?; do women and ethnic minorities have the same access to the labor market as everyone else?; how does the formal sector live alongside the informal sector?; what role does migration play in the functioning of labor markets?;and are there traits common to all urban labor markets in Africa, or is each country different? This book attempts to answer these questions by studying 11 cities in 10 countries (table O.1). Comparative studies are often based on disparate measurement instruments, which risk marring the validity of the findings. This study is based on a set of perfectly comparable surveys. The study also covers a number of topics (migration, child labor, job satisfaction, discrimination, and work after retirement) in addition to the topics covered by Lachaud (unemployment, access to employment and mobility, segmentation, labor supply, and poverty). This book is divided in five parts. The first is comparative analysis of urban labor markets in Sub-Saharan Africa; second is job quality and labor market conditions in Sub-Saharan Africa; third is dimensions of labor market inequalities; fourth is the key coping mechanisms and private responses; and fifth is moving forward.